Raiva: origem, importância e aspectos históricos - Babboni, Selene Daniela [UNESP]; Modolo, José Rafael [UNESP] (My University, 2011)
Rabies was described at least 4 millennia ago and is one of the oldest zoonosis. All mammals have cells which are responsible for viral replication, and they are the only ones susceptible to the virus and capable of transmitting it. Due to its lethal evolution, high number of human cases, as well as individuals yearly submitted to post-exposure rabies treatment, rabies remains a worldwide public health problem. The lack of adequate information systems and epidemiological surveillance in most countries does not allow us to know the true magnitude of the problem. The historical period of rabies is extended, because since Aristóteles, it was already considered a contagious disease and because of the bite of dogs, it was feared and known as a lethal disease. Louis Pasteur has provided a major breakthrough, which reached its climax with the first vaccination of a human being in 1885, as well as the creation of the Pasteur Institute in Paris in 1888. The chronology of reabies natural history in this review demonstrates the development in discoveries about the disease since its origin.

A raiva foi descrita pelo menos há 4 milênios e é uma das zoonoses mais antigas que se tem conhecimento. Todos os mamíferos possuem células competentes para a replicação viral, sendo estes os únicos suscetíveis ao vírus e os únicos capazes de transmiti-lo. Devido a sua evolução letal, ao elevado número de casos em humanos bem como de pessoas submetidas anualmente a tratamentos rábicos pós-exposição, a raiva continua sendo um problema mundial de saúde pública. A falta de sistemas adequados de informação e vigilância epidemiológica, na maioria dos países, não permite o conhecimento da real magnitude do problema. O período histórico da raiva é longo, pois desde Aristóteles essa doença já era considerada como enfermidade contagiosa e, devido à mordedura de cães, era temida e conhecida como uma doença letal. Louis Pasteur proporcionou enorme progresso, que alcançou seu ponto culminante com a primeira vacinação de um ser humano em 1885, bem como a criação do Instituto Pasteur de Paris, em 1888. A cronologia da história natural da raiva nessa revisão demonstra os avanços nos descobrimentos sobre a doença desde sua origem.
Rabies: origin, importance and historical aspects
Keywords: Rabies; Zoonosis; Epidemiology; Public health; Raiva; Zoonoses; Epidemiologia; Saúde pública